2015
DOI: 10.1111/jsm.12735
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Personality and Coping on Female Sexual Function: A Population Survey

Abstract: Introduction Female sexual dysfunction (FSD) is a common disorder with limited data investigating relationships with psychological influences, such as personality traits and coping mechanisms. Aim To investigate the relationship and impact of personality traits and coping strategies on female sexual function. Methods A web-based survey was distributed to a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…Studies have found that higher levels of Neuroticism and lower levels of openness relate to poorer sexual functioning in men and women [6,8,54,55]. Such results are more consistent with Kurpisz and collaborators and with Allen et al that suggest a role of high Neuroticism and Low Extraversion in erectile difficulties [53,50].…”
Section: Ed Correlation With Neuroticism and Extraversionsupporting
confidence: 80%
See 1 more Smart Citation
“…Studies have found that higher levels of Neuroticism and lower levels of openness relate to poorer sexual functioning in men and women [6,8,54,55]. Such results are more consistent with Kurpisz and collaborators and with Allen et al that suggest a role of high Neuroticism and Low Extraversion in erectile difficulties [53,50].…”
Section: Ed Correlation With Neuroticism and Extraversionsupporting
confidence: 80%
“…In North American and European samples, higher levels of Neuroticism, and lower levels of Extraversion and openness, have been found to relate to poorer sexual functioning [6,50,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, extraversion, openness to new experiences, emotional stability, and utilization of positive coping mechanisms were associated with better sexual function (Crisp et al, 2014). Moreover, in a very recent study, it was concluded that changes in female sexual response are closely tied to day-to-day fluctuations in happiness, enthusiasm, calmness, and fear.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…It can be said that in couples with SD, women partners have significantly higher cautious, shyness, skepticism, and pessimism, but lower responsibility, purposefulness, skillfulness, and self-esteem. In literature, certain personality traits in women are seen as risk factors to develop SD (21,46). Different results are encountered in very few studies made with TCI.…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted in clinical sampling with Five-Factor Model, it is found out that a relationship is found in women between sexual problems and higher neuroticism and lower extraversion (19), while neuroticism is the best distinguishing factor between men with and without SD (20). In studies conducted in nonclinical sampling, neuroticism and extraversion were found to be the variables best predicting the attitude to sexuality (14), and the variables of introversion, not being open to new experiences, emotional instability and neuroticism in women, and the variable of neuroticism in men were regarded to be risk factors for developing SD (21,22). These studies showed that sexual arousal and orgasm difficulties in women are strongly related to higher neuroticism and lower extraversion and orgasmic infrequency is strongly related to introversion, emotional instability and not being open to new experiences.…”
Section: Introductionmentioning
confidence: 95%